Qur'anic Principles of Educational Supervision: An Effort to Realize Quality Islamic Education - Decky Saputra; Badrun Fawaidi; Agus Salim Salabi (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
This article examines the application of Qur'anic principles in Islamic education supervision to improve the quality of education. Using a qualitative approach and conceptual analysis, this study focuses on identifying Qur'anic principles relevant to educational supervision, namely mas’ūliyyah (responsibility), amānah (trust), iḥsān (continuous improvement), syūrā (deliberation and collaboration), and taqwīm (evaluation). The literature selection process was based on the criteria of relevance, validity, credibility, and novelty of the sources. Data were collected through identification, selection, and review of relevant literature, followed by qualitative descriptive analysis through stages of Identification of Qur'anic Verses, Interpretation of Verses, Contextual Analysis, and Thematic Synthesis. The results show that these Qur'anic principles have both relevance and practical application in the context of Islamic education, in terms of both moral development and the enhancement of teacher competencies. Implementing these Qur'anic principles in educational supervision improves academic performance and fosters an academic culture based on moral and spiritual values. This study also demonstrates that synthesizing Qur'anic principles with modern educational theories contributes to the development of a transformative and collaborative supervision model aimed at enhancing educational quality.